2003
DOI: 10.1097/01.lab.0000090159.53224.b9
|View full text |Cite
|
Sign up to set email alerts
|

COX-2/VEGF-Dependent Facilitation of Tumor-Associated Angiogenesis and Tumor Growth in vivo

Abstract: SUMMARY:Nonsteroidal anti-inflammatory drugs are known to suppress the occurrence and progression of malignancies such as colorectal cancers. However, the precise mechanism of these actions remains unknown. We have evaluated the role of an inducible cyclo-oxygenase (COX-2) in tumor-associated angiogenesis and tumor growth, and identified the downstream molecules involved using a ddy mouse model of sponge angiogenesis, which mimics tumor angiogenesis and is COX-2 and vascular endothelial growth factor (VEGF) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 35 publications
4
46
0
1
Order By: Relevance
“…In the sponge model, granulation tissues with the property of chronic inflammation were formed around the sponge implants with enough reproducibility, and we can easily determine the active molecules at the site of the chronic inflammation, because rapid sampling and easy extractions of active molecules and mRNA can be performed in the sponge model. The results with this sponge model have been published in some journals, 5,6,26,27,29,[31][32][33][34][35][36][37][38][39][40] and many researchers have a strong interest in this model. In the beginning of this study, we had tried to test this sponge model to clarify the involvement of PGs in lymphangiogenesis during the chronic inflammation, but the detection of newly developed lymphatics was quite difficult in the sponge model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the sponge model, granulation tissues with the property of chronic inflammation were formed around the sponge implants with enough reproducibility, and we can easily determine the active molecules at the site of the chronic inflammation, because rapid sampling and easy extractions of active molecules and mRNA can be performed in the sponge model. The results with this sponge model have been published in some journals, 5,6,26,27,29,[31][32][33][34][35][36][37][38][39][40] and many researchers have a strong interest in this model. In the beginning of this study, we had tried to test this sponge model to clarify the involvement of PGs in lymphangiogenesis during the chronic inflammation, but the detection of newly developed lymphatics was quite difficult in the sponge model.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] Thus, future therapeutic strategies may involve controlling PG formation and receptor signaling. [27][28][29] However, the roles of PGs in lymphangiogenesis remain not fully clarified. 30 In the present study, we used Matrigel plugs to evaluate lymphangiogenesis during development of proliferative granulation tissues around the gels, although this Matrigel model was used for the evaluation of angiogenesis and cell migration assays.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 expression is associated with poor patient prognosis and survival (33,34). We previously reported that, in addition to tumor COX-2 expression, COX-2 present in stromal tissues had a significant effect on tumor-associated angiogenesis (35). Further studies showed that COX-2 induced lung metastasis via EP3 signaling (14).…”
Section: Resultsmentioning
confidence: 99%
“…NSAIDs inhibit enzymatic activity of cyclooxygenases (COX) whose products prostaglandins are known to inhibit apoptosis, stimulate tumor growth, and enhance angiogenesis, tumor cell invasion and metastasis in many cancer models (Connolly et al, 2002;Yoshida et al, 2003). NSAIDs, by inhibiting COX activity, enhance apoptosis and exert anti-metastatic and anti-angiogenesis effects, thereby inhibiting tumor growth.…”
Section: Introductionmentioning
confidence: 99%